Family lore eaudiobook A novel. - Acevedo, Elizabeth (HarperAudio, 2023)
NATIONAL BESTSELLER A GOOD MORNING AMERICA BOOK CLUB PICK! Winner of the NAACP Image Award, Outstanding Literary Work, Fiction Shortlisted for The Center for Fiction First Novel Prize From National Book Award-winning author Elizabeth Acevedo comes the story of one Dominican American family told through the voices of its women Flor has a gift: she can predict, to the day, when someone will die. So when she decides she wants a living wake—a party to bring her family and community together to celebrate the long life she's led—her sisters are surprised. Has Flor foreseen her own death, or someone else's? Does she have other motives? She refuses to tell her sisters, Matilde, Pastora, and Camila. But Flor isn't the only person with secrets: her sisters are hiding things, too. And the next generation, cousins Ona and Yadi, face tumult of their own. Spanning the three days prior to the wake, Family Lore traces the lives of each of the Marte women, weaving together past and present, Santo Domingo and New York City. Told with Elizabeth Acevedo's inimitable and incandescent voice, this is an indelible portrait of sisters and cousins, aunts and nieces—one family's journey through their history, helping them better navigate all that is to come. A Best Book of 2023 from: Washington Post * Good Housekeeping * Real Simple * Harper's Bazaar * Elle * Time * NPR